Factors Affecting Enterprise Resource Planning Adoption on Firms’ Performance among Medium-Sized Enterprises. - Adejare Aremu Yusuff; Arfan Shahzad; Shahizan Hassan (International Journal of Supply Chain Management, 2018)
the paper examined adoption of Enterprise Resource Planning (ERP) system to medium size enterprises organization as a method of using computer system technology to integrate all functions Department together, such as marketing, inventory control, accounting and human resource across an entire company. ERP system intends to facilitate information sharing, business planning, and decision making in enterprises organization. The objective of this paper is to propose a theoretical framework that determine factors that affecting ERP system adoption among medium size enterprises organization. The study proposes theoretical framework with the use of a developed questionnaire. The questionnaire was distributed to the various medium size enterprises firms of two hundred and seventeen (217) in Oyo State, Nigeria. The finding obtained from this study reveals that: ERP adoption significantly improve firms performance. Organizational structure has significant influence on ERP system adoption as to improve performance of medium size enterprises firms and technological change also significantly influence ERP system adoption for better performance of medium size enterprises firms. Therefore, effectiveness of ERP system adoption would improve firms performance. The result of this study can fill the gap in the literature on the organizational structure and technological change on ERP system adoption and its relationship with firms performance among medium size enterprises organization in Oyo State, Nigeria. Keywords Enterprise resource planning, Organizational Structure, Technological Change, Firms Performance, Medium size enterprises firm, Oyo State, Nigeria.